Emergent questions in bioethics - Sgreccia, Elio (Medicina e Morale, 1995)
The article deals with the roots of the problems emerging today in the field of bioethics (e.g. abortion, euthanasia, reproductive technologies, etc.). First of all the author points out that bioethics has increased the area of its influence by reaching beyond the boundaries of a purely academically qualified science. In fact it has involved the media on one hand and has created its own institutions (e.g. the institutional review boards) on the other hand. Bio-law is a relevant phenomenon, which is both a development following bioethical debate and a result of the ethical problems which exist in the field of the law. This increasingly highlights the complex relationship between moral values and the civil law in a pluralistic society. The problem of the foundations of bioethics, given the present ethical pluralism, is another important issue. Therefore the author comments on all the present ethical "models" and briefly illustrates their characteristics and limits, and in the end he finds that bioethics needs to discover its roots in personalistic anthropology based on an objective and universal truth. The article concludes by underlining the need to reconstruct "bridges" in order to establish the course of a more complete humanism: the bridge between faith and reason; the one between freedom and responsibility; the one between nature and person; the bridge between ethics and the law, and finally, the bridge between the Principles-based Bioethics and Virtues-based Bioethics.